Metatheory: Towards Creative Horizons in Strategic Management Conflicting Rules Theory (CRT) as a model - Alshahrani, Abdullah O.; Alofan, Fahad H. (The Arab Journal of Administration, 2025)
In light of the rapid changes in the current business environment and the prevalence of doubt and uncertainty in the era of globalization, organizations need explanatory models to anticipate the future and enhance the capabilities of strategic management in decision-making. To overcome the dilemma that has preoccupied strategic thinkers, that is, accurately predicting future events to implement appropriate strategic plans to improve organizational performance and achieve long-term goals; this study provides a roadmap towards new horizons in strategic management. It does so by adapting administrative, social, and humanitarian theories that are typically not applicable in the strategic field, utilizing their predictive capabilities to serve strategic management. The study stipulates that two main conditions must be met: predictability and the derivation of hypotheses and empirical generalizations. It recommends integrating organizational knowledge into a cohesive framework that leads to managerial benefits. The study aims to formulate metatheories that benefit from theories derived from various scientific fields, enabling the prediction of factors that support strategic thought. This approach empowers decision-makers to move beyond existing theories to develop effective strategic plans that serve both strategic foresight and strategic management. The study demonstrates this method by using the theory of conflicting rules—a theory from the social sciences—as an applied model for its objectives.